Stanowisko duchownych Pomorza Gdańskiego wobec Grudnia 1970 w świetle dokumentów SB. Próba charakterystyki - Abryszeński, Piotr (Dzieje Najnowsze, 2015)
The Attitude of the Clergy from Gdańsk Pomerania towards the December 1970 Events in the Light of Security Service Documents. An Attempted Characteristic The tragedy, which took place in 1970 in the streets of Gdańsk and Gdynia, became a prominent point of reference for relations between the state and the Catholic Church. Although at the time of the December events members of the clergy preserved a certain distance towards the incidents, they were interested in their course and became involved in appealing for the preservation of order. The calls aimed predominantly at avoiding an escalation of tension and protecting the health and lives of innocent people. Prayers were said for the victims and the restoration of peace. Already in December 1970 the diocese of Gdańsk started to organise spiritual and material support for the families of the murdered and the wounded. At the beginning of the next year assistance assumed a more organised form and involved the bishops of Gdańsk – Edmund Nowicki and Lech Kaczmarek, as well as Bishop Kazimierz Kowalski of Chełmno. The power crisis simultaneously increased the growth of the influence enjoyed by the Church. The communist authorities indubitably tried to exploit the firm position of the Church for the purpose of legitimising their policy in the eyes of Polish society. The Security Service embarked on a parallel intensification of its activity vis a vis the clergy, i.e. by observing assorted attitudes or recording opinions about the December events, expressed both in the course of Holy Mass and in private conversations. Views voiced by priests affected the attitude towards the communist authorities, while familiarity with such opinions served not merely a portrayal of the moods and tendencies prevailing among the clergy. The apparatus of repression was capable of stifling eventual symptoms of disapproval and a criticism of the system, e.g. by resorting to threats or warnings formulated in the course of talks. One of the documents declares that younger clergymen approved the workers’ protests in contrast to older priests, a feature distinctive for the December events. The consequences of the alleviation of social moods included a normalisation of state–Church relations. The authorities regarded the course of talks held both at a central and a local level as vital. The bishops too tried to exploit such dialogues for resolving questions broached for years, such as the erection of churches or the restitution of Church property seized by the communists.